Pemanfaatan Website Sebagai Media Promosi Pada Fakultas Teknologi Informasi dan Komunikasi Universitas Semarang - Vydia, Vensy (Universitas Semarang, 2009)
Website are one information system whatever available on webbed server that enable web visitor to access available information. Website can give information of one as text, still image until pictured animations, multimedia's voice, video. Website. dynamic is website one that can provide feedback to page as is visitor expects a guest that enable visitor to give tips and comment, and also criticism.Promotion and information moment to using to introduces a product and service to extensive society. After been ·designed and is made one website that interactive and. dynamic expected society will get more complete information about Information Technology and Communication Faculty in Semarang University. E.g; profile, vision and mission, lecturer, college student, collegiate, aught facility etc. So aim of makings · website can materialize.